Put science first and formatting later. (12th April 2018) - Khan, Aziz; Montenegro‐Montero, Alejandro; Mathelier, Anthony
Abstract : Scientists spend considerable efforts with reformatting their research articles before each new submission. A widely adopted format‐free submission process would save them valuable time to do research instead.